The Effect of Work Motivation and Work Discipline on Employee Performance in Home-Based Bakery Businesses in Padang City with Job Satisfaction as a Mediating Variable - Farra Qayla Rinjani; Muhammad Oceano Fauzan (SAFE-Network, 2026)
This study aims to examine the effect of work motivation and work discipline on employee performance in home-based bakery businesses in Padang City, with job satisfaction as a mediating variable. The research employs a quantitative approach using a causal method. The population consists of all employees from five home-based bakeries in Padang City, namely SF Bakery, Adeng, Bintang Kejora, Husna, and Rafi, with a total sample of 35 respondents selected through total sampling technique. Data were collected using a Likert-scale questionnaire and analyzed through multiple regression analysis and hypothesis testing. The findings reveal that work motivation and work discipline have a positive and significant effect on job satisfaction. Job satisfaction also has a positive and significant effect on employee performance. Furthermore, work discipline significantly influences employee performance, while work motivation does not have a direct significant effect on performance. However, work motivation indirectly affects employee performance through job satisfaction as a mediating variable. Similarly, work discipline also has an indirect effect on employee performance through job satisfaction. The study concludes that job satisfaction plays a crucial role as a mediating variable in improving employee performance. Therefore, enhancing work motivation and discipline should be accompanied by efforts to improve job satisfaction in order to achieve optimal employee performance.